Pengaruh Kompetensi dan Disiplin terhadap Kinerja Pegawai pada Kantor Camat Sitinjau Laut Kabupaten Kerinci - Fahdillah, Yosi; Herlina, Vivi (Ebisma (Economics, Business, Management, & Accounting Journal), 2025)
This study aims to examine the influence of competence and discipline on employee performance at the Kecamatan Sitinjau Laut Kabupaten Kerinci, both simultaneously and partially, and to identify the most dominant variable affecting performance. The research questions focus on whether competence and discipline significantly affect employee performance, the extent of their influence, and which variable contributes most prominently. The analysis is based on indicators representing competence and discipline and their relationship to performance outcomes. The findings indicate that competence positively influences employee performance, as supported by relevant statistical tests. Discipline also contributes to performance improvement, though with a different level of impact compared to competence. When analyzed simultaneously, both variables show a significant effect on employee performance, as demonstrated through regression analysis. Among the two, competence emerges as the more dominant factor. These results suggest that enhancing employee competence and reinforcing workplace discipline are effective strategies for improving performance in local government institutions.